Fundus Autofluorescence in Chronic Essential Hypertension - Alireza Ramezani; Peyman Saberian; Masoud Soheilian; Saeed Alipour Parsa; Homayoun Koohi Kamali; Morteza Entezari; Mohammad-Mehdi Shahbazi; Mehdi Yaseri (Journal of Ophthalmic & Vision Research, 2014)
Purpose: To evaluate fundus autofluorescence (FAF) changes in patients with chronic essential hypertension (HTN). Methods: In this case-control study, 35 eyes of 35 patients with chronic essential HTN (lasting >5 years) and 31 eyes of 31 volunteers without history of HTN were included. FAF pictures were taken from right eyes of all cases with the Heidelberg retina angiography and then were assessed by two masked retinal specialists. Results: In total, FAF images including 35 images of hypertensive patients and 31 pictures of volunteers, three apparently abnormal patterns were detected. A ring of hyper-autofluorescence in the central macula (doughnut-shaped) was observed in 9 (25.7%) eyes of the hypertensive group but only in 2 (6.5%) eyes of the control group. This difference was statistically significant (P = 0.036) between two groups. Hypo- and/or hyper-autofluorescence patches outside the fovea were the other sign found more in the hypertensive group (22.9%) than in the control group (6.5%); however, the difference was not statistically significant (P = 0.089). The third feature was hypo-autofluorescence around the disk noticed in 11 (31.4%) eyes of hypertensive patients compared to 8 (25.8%) eyes of the controls (P = 0.615). Conclusion: A ring of hyper-autofluorescence in the central macula forming a doughnut-shaped feature may be a FAF sign in patients with chronic essential HTN.